Molecular analysis of patients of Sardinian descent with Crigler-Najjar syndrome type I. Issue 2 (February 1997) - Rosatelli, M C; Meloni, A; Faa, V; Saba, L; Crisponi, G; Clemente, M G; Meloni, G; Piga, M T; Cao, A
Abstract : This study reports the molecular characterisation of the bilirubin UDP-glucuronosyl-transferase gene (UGT1) in a group of patients of Sardinian descent with Crigler-Najjar syndrome type I and their relatives. Sequence analysis of both UGT1A exon 1 and common exons 2-5 was performed in all patients, leading to the detection of AF170 and a novel mutation (470insT), both residing in UGT1A exon 1. All but two heterozygotes for the AF170 mutation showed normal serum bilirubin levels. These two subjects were also heterozygous for the sequence variation A(TA)7TAA in the promoter region of the UGT1A gene.